An investigation on the indoor air quality of main lecture halls in UiTM Shah Alam Campus / Nurashikin Rabu - Rabu, Nurashikin (2010)
Indoor air quality (IAQ) is referring to the air quality within and around buildings and structures, especially as it relates to the health and comfort of building occupants. Determination of IAQ involves the collection of air samples, monitoring human exposure to pollutants, collection of samples on building surfaces and computer modeling of air flow inside buildings. In addition, indoor air quality (IAQ) also refers to the quality of the air inside buildings as represented by concentrations of pollutants and thermal (temperature and relative humidity) conditions that affect the health, comfort, and performance of occupants. Other factors affecting occupants, such as light and noise, are important indoor environmental quality considerations. The title of this research is 'An Investigation on the indoor Air Quality of Main Lecture Halls in UiTM Shah Alam' covers a indoor air quality at the main lecture hall in UiTM Shah Alam campus carry out the survey in the method of questionnaire and testing in order to complete this final projects. The aim of this research is to identify the symptoms from the level of indoor air quality (IAQ) in case study building. This aim can be achieve by carry out the survey in the method of questionnaire for building occupants at the lecture halls and this research also to examine the contaminants that contributes to the poor indoor air quality (IAQ) and to recommend the suitable thermal comfort criteria for lecture hall in UiTM Shah Alam Campus. This aim can be achieved by carry out the survey in the method of questionnaire and testing for humidity, illumination, and air temperature and air particles at the lecture halls.